2021
DOI: 10.1158/1078-0432.ccr-20-3646
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial of Anthracycline-free and Anthracycline-containing Neoadjuvant Carboplatin Chemotherapy Regimens in Stage I–III Triple-negative Breast Cancer (NeoSTOP)

Abstract: Purpose: Addition of carboplatin (Cb) to anthracycline chemotherapy improves pathologic complete response (pCR), and carboplatin plus taxane regimens also yield encouraging pCR rates in triple-negative breast cancer (TNBC). Aim of the NeoSTOP multisite randomized phase II trial was to assess efficacy of anthracycline-free and anthracycline-containing neoadjuvant carboplatin regimens. Patients and Methods: Patients aged ≥18 ye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 33 publications
0
47
2
1
Order By: Relevance
“…Subgroup analysis revealed a larger magnitude of benefit in patients with earlier clinical stage [86]. In the NeoSTOP study, pCR rates were found to be similar between the anthracyclinecontaining versus anthracycline-free arm, with also similar EFS and OS [87]. As expected, the anthracycline-free arm was associated with higher rates of treatment completions and lower health-related costs.…”
Section: Omission Of Anthracyclines Triple Negative Breast Cancermentioning
confidence: 57%
“…Subgroup analysis revealed a larger magnitude of benefit in patients with earlier clinical stage [86]. In the NeoSTOP study, pCR rates were found to be similar between the anthracyclinecontaining versus anthracycline-free arm, with also similar EFS and OS [87]. As expected, the anthracycline-free arm was associated with higher rates of treatment completions and lower health-related costs.…”
Section: Omission Of Anthracyclines Triple Negative Breast Cancermentioning
confidence: 57%
“…As a result, National Comprehensive Cancer Network (NCCN) guidelines have added weekly paclitaxel plus carboplatin or docetaxel plus carboplatin regimens for select patients with TNBC in the preoperative setting 18 . Recently published NeoSTOP study was con rmed that the pCR and RCB 0 + 1 rates of carboplatin plus docetaxel (CbD) were similar to carboplatin plus paclitaxel followed by doxorubicin plus cyclophosphamide 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Another published meta-analysis evaluating the role of platinum salts in BRCA mutated TNBC patients showed that adding platinum increases pCR rate without statistical significance [ 66 ]. Recently published prospective trial NeoSTOP evaluated carboplatin-containing NACT presented a higher pCR rate in BRCA mutated TNBC patients on the borderline of significance, but this study included only platinum-based regimens [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the GeparSixto trial, the addition of carboplatin was associated with a higher rate of hematological and non-hematological toxicity, and the dose of carboplatin was reduced from AUC 2.0 to AUC 1.5 [ 29 ]. On the other hand, a more favorable toxicity profile was observed for the AC-free carboplatin regimen in the NeoSTOP trial [ 67 ]. According to our study results, toxicity was more common in patients with platinum NACT but especially lower grades.…”
Section: Discussionmentioning
confidence: 99%